Knowledge of medical cannabis use, cannabis in food, and health literacy among late-adolescent students in a Thai province - Poonphol, Prasittichai; Thanawiroon, Charuwan; Soontara, Chaisit; Thammakittiphan, Supaphit; Kulbunya, Soraya; Dalas, Chanathip; Kunnamas, Janjaree; Phohom, Tawanchai; Chaksupa, Narongchai; Khumsikiew, Jeerisuda; Supapaan, Teeraporn Sadira (Iraqi Journal of Pharmaceutical Sciences, 2026)
Cannabis is the most widely used illicit drug globally, with an increasing use for both medicinal and non-medical purposes. Despite evolving policies and regulations, knowledge gaps persist among the youth, particularly regarding cannabis use, its integration into food products, and associated health risks. Many adolescents rely on unverified sources such as social media and peer networks for cannabis-related information, thereby increasing the risk of misinformation and unsafe consumption. This cross-sectional descriptive study assessed knowledge levels with respect to medical cannabis use, cannabis in food, and health literacy among late adolescent students in educational institutions. Additionally, it examined factors influencing knowledge, experience, and willingness to try cannabis while exploring opinions on medical cannabis use and cannabis in food. Data were collected from 252 students aged 15 - 18 years, using self-administered questionnaires. Descriptive statistics were used to analyze participant characteristics, while the chi-square test was applied to assess relationships between demographic factors, knowledge, and health literacy. The Decision Tree method (CART Algorithm) identified key determinants, classified participants based on significant factors, and predicted cannabis use and abstinence. The findings revealed that 49.2% of the participants had low cannabis-related knowledge, whereas 62.3% demonstrated moderate health literacy. Gender and field of study significantly influenced knowledge and health literacy. Most of the participants acknowledged the benefits and risks of cannabis use. These results highlight the need for targeted educational interventions to enhance cannabis-related knowledge and health literacy among late adolescents, considering their unique contexts and experiences.